2020
DOI: 10.1021/acs.iecr.0c01900
|View full text |Cite
|
Sign up to set email alerts
|

Breathable, Stimuli-Responsive, and Self-Sealing Chemical Barrier Material Based on Selectively Superabsorbing Polymer

Abstract: The occasional use of chemical warfare agents (CWAs) by rogue states in current conflicts provides a reminder that these hazards are a real threat. Although hazmat suits made of fully impermeable barrier materials provide an effective means of protecting against CWAs, they also inhibit evaporative cooling which can cause rapid hyperthermia. This conundrum has motivated a search for novel materials that allow water vapor but not CWA permeation. Here we show that, at least for aerosolized CWA, this can also be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Moreover, as physical adsorption is reversible, it may result in re-emission of CWA. An alternative to these materials is to develop reactive breathable materials (Bui, et al, 2016) (Chuang, Hong, & Chang CT, 2014) (Vanangamudi, Hamzah, & Singh, 2015) (Satilmis & Uyar, 2018) (Manning, Kotagama, Burgin, & Rykaczewski, 2020) which can adsorb and destroy TICS and CWAs. Incorporating nucleophile groups onto the surface of the material will enable a chemical response to CWA attack based on hydrolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as physical adsorption is reversible, it may result in re-emission of CWA. An alternative to these materials is to develop reactive breathable materials (Bui, et al, 2016) (Chuang, Hong, & Chang CT, 2014) (Vanangamudi, Hamzah, & Singh, 2015) (Satilmis & Uyar, 2018) (Manning, Kotagama, Burgin, & Rykaczewski, 2020) which can adsorb and destroy TICS and CWAs. Incorporating nucleophile groups onto the surface of the material will enable a chemical response to CWA attack based on hydrolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Then, hydrophobic microporous membranes, represented by PTFE membranes (such as Gore-Tex) [102], are constructed to act as a filter to block pollutants. A major breakthrough in WBM fabrics is the development of self-sealing fabrics [103], which can solve the problem of reduced waterproofness and breathable performance caused by internal WBM damage after sewing on coats, tents, etc.…”
Section: Daily Outdoor Sportswearmentioning
confidence: 99%
“…Breathable self‐sealing composite fabric containing dispersed microparticles of a selectively super absorbing polymer (SAP) can defend against aerosolized nerve and blistering CWAs. In normal conditions, the SAP microparticles dispersed on a nylon mesh provide WVTR over 10 kg m −2 day −1 while upon contact with fog from CWA aerosolization, permeation of CWA micro‐droplets is prohibited due to swelling of microparticles, which leads to pores sealing 238 . It was reported that loading polyelectrolyte membranes (Nafion 117 and Nexar MD9200) with ZnO NPs significantly reduces dimethyl methyl phosphonate (a nerve agent simulant) permeation 239 …”
Section: Protective Membranesmentioning
confidence: 99%